Decoding community murals as visual representations of multiculturalism in Suryatmajan tourism kampong - Oentoro, Kristian; Sunarya, Yan Yan; Nugraha, Adhi; Ihsan, Muhammad (International Journal of Culture and Art Studies, 2025)
Community murals, as participatory public art projects, express local identities and cultural influences within society. Situated in the heart of Yogyakarta, the community mural in Suryatmajan tourist village conveys a visual message about unity in diversity while promoting a multicultural ideology. Therefore, this study aims to analyze the signs on these community murals as visual representations of multiculturalism. Employing Roland Barthes’ semiotic analysis, this research decodes the signs and layered meanings in four murals placed at the different entrance gates. These murals visually represent four distinct cultural influences, from local to global: Javanese, Chinese, Japanese, and American (popular culture). These cultural influences are identified through images of prominent figures or icons associated with each culture. They generate denotative and connotative meanings for each mural according to its story. As a manifestation of community engagement, the diversity in this mural representation reflects social conditions, cultural history, and residents’ preferences. These murals also demonstrate the community’s tolerance for cultural differences and foster multiculturalism. By prioritizing the value of harmony (guyub), Suryatmajan tourism kampong emphasizes unity in cultural diversity as a mural narrative. This research concludes that the community mural in tourism kampong is more than simply decoration; it serves as a collective expression, attracts tourists, and fosters multiculturalism within the society.